The Role of Boredom Proneness in Moderation of The Relationship between FoMO and Phubbing Behavior of Yogyakarta's Gen-Z - Eva Nur Fadillah; Zahro Varisna Rohmadani (Journal of Islamic Psychology and Behavioral Sciences, 2026)
The rapid advancement of social media has given rise to the phenomenon of phubbing , which is the tendency for someone to ignore social interactions around them because they are too focused on using their mobile phone. This phenomenon is often associated with Fear of Missing Out (FOMO) and Boredom Proneness . The purpose of this study is to analyze the influence of FOMO on phubbing behavior with Boredom Proneness as a moderating variable on Gen-Z social media users in Yogyakarta. This study uses a quantitative approach by conducting a survey of 215 respondents determined through a purposive sampling technique . Data collection was carried out through a questionnaire with a Likert scale, then analyzed using descriptive tests, classical assumption tests, path analysis, and Moderated Regression Analysis (MRA). Based on the results of the analysis that has been done, it shows that FOMO has a positive and significant effect on phubbing behavior (β = 0.302; p = 0.004). In addition, Boredom Proneness also plays a significant role as a moderator that strengthens the relationship between FOMO and phubbing (β = 0.319; p = 0.003). This means that the higher the FOMO and boredom tendency, the more likely an individual is to engage in phubbing. This study is limited by the number of respondents who did not meet the ideal target, where only 215 respondents were collected from the target of 400 people . Therefore, it is recommended that further research involve a larger and more diverse sample. Theoretically, this study enriches the understanding of the psychological factors of the digital behavior of the younger generation, while practically, the results can be the basis for developing digital literacy and self-regulation to reduce phubbing behavior among Gen-Z.